2016
DOI: 10.3390/rs8040297
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multiple Datasets for Monitoring Thermal Time in Urban Areas over the U.S. Upper Midwest

Abstract: Traditional studies of urban climate used air temperature observations from local urban/rural weather stations in order to analyze the general pattern of higher temperatures in urban areas compared with corresponding rural regions, also known as the Urban Heat Island (UHI) effect. More recently, satellite remote sensing datasets of land surface temperature have been exploited to monitor UHIs. While closely linked, air temperature and land surface temperature (LST) observations do not measure the same variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The daytime SUHII in summer was the strongest, while daytime SUHII in winter showed a contrary urban cool island phenomenon. This strongest daytime SUHI phenomenon in summer from this study is consistent with previous studies about most of the China cities [40,41], Seoul and Tokyo [38], most of the central European cities [43], and most of the USA cities [28,65]. However, the cities with surface urban cool island are usually distributed in Northern China [40,41] and high latitudes of the Northern Hemisphere (e.g., 55 • N-60 • N) [10].…”
Section: Possible Mechanisms Of Seasonal Suhii Variationssupporting
confidence: 81%
See 2 more Smart Citations
“…The daytime SUHII in summer was the strongest, while daytime SUHII in winter showed a contrary urban cool island phenomenon. This strongest daytime SUHI phenomenon in summer from this study is consistent with previous studies about most of the China cities [40,41], Seoul and Tokyo [38], most of the central European cities [43], and most of the USA cities [28,65]. However, the cities with surface urban cool island are usually distributed in Northern China [40,41] and high latitudes of the Northern Hemisphere (e.g., 55 • N-60 • N) [10].…”
Section: Possible Mechanisms Of Seasonal Suhii Variationssupporting
confidence: 81%
“…Although the pattern of daytime SUHII was consistent with prior research and with less uncertainty [28,38,40,41,43,65], relatively large uncertainty existed in the pattern of nighttime SUHII. The nighttime SUHII in summer was lowest, which was consistent with most of the previous studies [40,66,75], but not consistent with the study of [76].…”
Section: Uncertaintiessupporting
confidence: 72%
See 1 more Smart Citation
“…Near‐surface air temperature is of greater importance than LST in terms of human health and comfort, which in the case of Boston have been reported from 0.13°C (spring daytime) up to 2.9°C (summer nighttime) higher in urban areas compared to rural (Wang et al, ). The relationship between LST and near‐surface air temperature in the UHI is complex, and can vary greatly depending on diurnal and seasonal timing and on characteristics of the underlying land surface fabric (Krehbiel & Henebry, ; Wang et al, ). Given these complexities, the specific contribution of albedo changes to land‐ or near‐surface temperature differences across this region cannot be precisely modeled with the data prepared for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, urban areas are usually warmer than nearby rural areas, a phenomenon recognized as the Urban Heat Island (UHI) effect [3,4]. Studies have shown that the environmental impacts of urban areas can extend well beyond administrative boundaries [5,6], and urban heat islands can increase the health risk of vulnerable populations to heat waves [7]. Intensity of the UHI effect depends on many factors, including building density, height, and arrangement; thermal and reflective properties of construction, paving, and roofing materials structures; size and arrangement of green spaces within the city; local and regional wind fields; season and time of year; and recent weather [7,8].…”
Section: Introductionmentioning
confidence: 99%